Comparison of lithotripsy methods during mini-PNL: is there a role for ballistic lithotripsy in the era of high-power lasers - Muhammed Arif Ibis; Ahmet Furkan Özsoy; Mehmet Fatih Özkaya; Emre Erdem; Serhat Erkmen; Ahmet Doruk Güler; Mehmet İlker Gökce (BMC Urology, 2024)
Abstract Background For renal stones > 20 mm, percutaneous nephrolithotomy (PNL) offers the best stone clearance rates with acceptable complication rates. This study aimed to compare the efficiency of high-power holmium YAG laser and ballistic lithotripsy during mini-PNL. Methods Data from 880 patients who underwent mini-PNL for renal stones was investigated retrospectively. The study utilized propensity score matching to create two groups: laser lithotripsy (n = 440) and ballistic lithotripsy (n = 440). The groups were matched based on stone size, Guy’s stone score, and stone density. The main objectives of the study were to assess the stone-free rate (SFR), duration of surgery, and complication rates. Results The average age of the population was 51.4 ± 7.1 years, with a mean stone size of 28.6 ± 8.3 mm and a mean stone density of 1205 ± 159 HU. There were no significant differences between the groups. The SFRs of the laser lithotripsy and ballistic lithotripsy were 92.5% and 90.2%, respectively (p = 0.23). The laser lithotripsy group had a notably shorter surgery time (40.1 ± 6.3 min) compared to the ballistic lithotripsy group (55.6 ± 9.9 min) (p = 0.03). Complication rates were similar (p = 0.67). Conclusions Our study shows that a high-power holmium YAG laser provides quicker operation time compared to ballistic lithotripsy. However, ballistic lithotripsy is still an effective and safe option for stone fragmentation during mini-PNL. In places where a high-power holmium YAG laser is not available, ballistic lithotripters are still a safe, effective, and affordable option for mini-PNL.